Principal Management in Improving Infrastructure in Junior High Schools - Akmal, Fauzi; Guspita, Rosi; Hafis, Ardian (Khalaqa: Journal of Education and Learning, 2024)
One indicator of whether a school is of good quality can be seen from the completeness of its educational facilities and infrastructure in supporting the learning process at school. The better and more complete the educational facilities and infrastructure in a school, the better the public's perception of the quality of the school. This research aims to determine the planning, implementation, evaluation, and obstacles encountered by school principals in managing infrastructure. This research uses field research. The informants were the Padang City Junior High School, especially the Foundation Leaders (Principals) of the Junior High School. The author collected data using observation, interviews, and documentation. Meanwhile, for data processing and analysis, the author did as mentioned by Creswell. The results of the research show that the implementation of infrastructure by the principal in junior high schools has been used according to its function even though the facilities and infrastructure in this school are not yet fully able to accommodate students' needs, such as the absence of a place of worship (mashallah) in the school and other facilities.